2016
DOI: 10.47604/ijfa.145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Consumer Protection Function on Financial Performance of Saccos in Kenya

Abstract: Purpose: The study sought to determine the effect of consumer protection function on financial performance of SACCOs in Kenya.Methodology: The study adopted a descriptive research design. The target population comprised of registered 181 deposit-taking SACCOs as at 31st December 2014 and the three licensed CRBs in Kenya. Stratified random sampling was used in the study, where SACCOs were grouped into five respective strata which were then randomly selected. The SACCOs were grouped into five respective strata o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…From table 7, it can be revealed that 27% agree that modification of Sacco products strategy has been adopted to a very great extent, 43.2% agree that the adoption is on great extent, 10.8% agree that the adoption is moderate, 8.1% agree that modification has been adopted to some extent while 10.8% agree that the modification of products has not been adopted. 35.1% of the respondents agree that diversification of products has been adopted to a very great extent, 13.5% agree that the adoption is to a great extent, 32.4% agree that the adoption is moderate, 16.2% agree that the adoption is of some extent while 2.7% agree that there is no adoption of diversification of products strategy.…”
Section: Product Development Strategymentioning
confidence: 98%
See 2 more Smart Citations
“…From table 7, it can be revealed that 27% agree that modification of Sacco products strategy has been adopted to a very great extent, 43.2% agree that the adoption is on great extent, 10.8% agree that the adoption is moderate, 8.1% agree that modification has been adopted to some extent while 10.8% agree that the modification of products has not been adopted. 35.1% of the respondents agree that diversification of products has been adopted to a very great extent, 13.5% agree that the adoption is to a great extent, 32.4% agree that the adoption is moderate, 16.2% agree that the adoption is of some extent while 2.7% agree that there is no adoption of diversification of products strategy.…”
Section: Product Development Strategymentioning
confidence: 98%
“…Kenya has 6,750 registered SACCOs with a membership of over 3 million [35]. Kenyan SACCOs play a vital role in wealth creation, poverty alleviation, employment, and development of the society.…”
Section: Background To the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…During the implementation of a strategy, several variations frequently occur in organizations, with their main impacts being on the strategy's success. According to Ingow and Opuodho (2019), a defined growth strategy is essential for SACCOs to realize their growth opportunities. Corporate strategy, according to Esokomi, et al (2020) fundamentally affects a firm's direction and all of its managerial practices.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it has been demonstrated in prior study by Hamisi, & Gichinga,(2020) that the three strategic management phases of strategy creation, strategy implementation, and evaluation and control are crucial to the success of cooperatives. Ingow, & Opuodho, (2019) contend that organizational strategy must specify the organization's future goals while taking into account available options, resources, and other alternatives. In this situation, companies must first recognize and comprehend the internal resources, talents, strengths, and weaknesses that they possess in order to develop strategies (Tukamuhebwa, et al 2022).…”
Section: Introductionmentioning
confidence: 99%